PHYSICO-CHEMICAL STUDY CONCERNING ATMOSPHERIC PARTICULATE MATTER HAZARD - PETEAN, Ioan; MOCANU, Aurora; PALTINEAN, Gertrud Alexandra; ŢĂRCAN, Raluca; MUNTEAN, Dana Florina; MUREŞAN, Liana; ARGHIR, George; TOMOAIA-COTISEL, Maria (Studia Universitatis Babeș-Bolyai Chemia, 2017)
The particulate matter (PM) from the atmosphere is able to penetrate the respiratory system presenting several health risks such as acute respiratory items, allergic issues, and chronic risks such as silicosis and asthma. PM from atmosphere is classified by diameter as PM10 – particles with aerodynamic diameter up to 10 µm, PM2.5 – particles with aerodynamic diameter up to 2.5 µm, and PM1 - particles with aerodynamic diameter up to 1 µm. The first major PM source is the street dust (SD) which induces mineral fraction into the atmosphere such as: quartz, kaolinite, calcite, muscovite, and goethite. The second PM source is the pollen from several species like Tilia Cordata, Sambucus Nigra, Jasminus Communis, Rosaceae Family, Lilium Candidum, and Brassica Rapa, during later spring and early summer. Elements from both sources were found in PM samples collected from atmosphere: sedimentary particles, PM10 and PM2.5. In vivo experiments show that PM10 affects upper respiratory pathways such as nasal cavity and pharynges meanwhile PM2.5 was found in the expectoration matter from tracheal area. These studies reveal that 5 minutes of exposure at a concentration of 125 µg/m3 conducts to formation of severe deposits on respiratory mucosa.